Expansion Velocities of Elementary Gas in Comet Panstarrs Above 30000 Km from Nucleus - Khalaf, Salman Z.; Abrahim, Khaleel (Iraqi Journal of Science, 2020)
The coma gasses consist of molecules liberated from the nucleus by solar heating and relative sublimation. Once they have left the nucleus, these molecules in the coma are exposed to direct solar radiation and can be damaged in various ways due to the combined action of these reactions. One of some complex problems facing the research in this field is that the Maxwell-Boltzmann equation gives distribution function for one kind of particles which have same masses, but the gas has multi-groups of particles (Carbon, Neon, Sodium … etc.), where all these components must be in one program to extract average velocity of all and calculate particles velocity to each band. This problem is solved here by Matlab program and the approach demonstrated good results. The study included extracting some elements of comet PanSTARRS by using X-ray spectrum with the calculation of elements’ abundances in respect to Carbon and obtaining particles’ velocity distribution to calculate most of the particles in the intervals of velocities. The study shows some physical relationships of cometary heavy elements, which are larger in mass than Carbon and have roughly less abundance in the cometary gases. Using X-ray spectrum, 23 elements of comet PanSTARRS C/2011 S4 were obtained. Carbon showed the highest abundance, followed by Gold. Apparent abundance of all elements were extracted in respect to Carbon, which was correlated with the distribution function of Maxwell-Boltzmann to calculate element velocities and the bands of most particles’ velocities. Gas temperature was found to be equal to 1412 k. From this value, the velocity of each particle was obtained, as shown in the figures, where the velocity range of most particles (about 21% of total particles) was 400-600 m s-1, whereas extending the band to 200-800 m s-1 showed that the abundance includes 54% of particles. An H2O curve peak was found at velocity of 1142 m s-1, while the highest value was 1389 m s-1 for Carbon (relatively light element) and the lowest value was about 340 m s-1 for Gold particles (relatively heavy element).